2021
DOI: 10.1159/000517832
|View full text |Cite
|
Sign up to set email alerts
|

Remission of Alopecia Universalis after 1 Year of Treatment with Dupilumab in a Patient with Severe Atopic Dermatitis

Abstract: Alopecia areata (AA), an autoimmune disease with a relapsing-remitting course, represents the second cause of non­scarring alopecia worldwide and is associated with several comorbidities, notably atopic dermatitis (AD). In particular, AD is related to its more severe forms alopecia totalis (AT) and alopecia universalis (AU) [Nat Rev Dis Primers. 2017;3:17011]. Considering that AA has been classified as T helper 1-driven disease, whereas AD is the prototypical T helper 2 (Th2)-driven skin disorder, recent studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…At the end of week 24, 10% (4/40) of patients in the treatment arm achieved SALT 50 compared to none in the placebo arm (Table 4). These results corroborated the findings from multiple case‐series studies and case reports demonstrating the potential efficacy of dupilumab 49–52 …”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…At the end of week 24, 10% (4/40) of patients in the treatment arm achieved SALT 50 compared to none in the placebo arm (Table 4). These results corroborated the findings from multiple case‐series studies and case reports demonstrating the potential efficacy of dupilumab 49–52 …”
Section: Resultssupporting
confidence: 87%
“…These results corroborated the findings from multiple case-series studies and case reports demonstrating the potential efficacy of dupilumab. [49][50][51][52] Despite the encouraging results, multiple studies have also reported on the paradoxical of dupilumab in the development, exacerbation or reactivation of AA. [53][54][55][56] The inhibition of IL-4 may skew the CD4 + T cells towards the T helper 1/T helper 17 type response, which have been implicated in the immunopathogenesis of AA (Figure 2).…”
Section: Clinical Studiesmentioning
confidence: 99%
“…One case of incontinentia pigmenti-associated scalp alopecia was reported. Clinical responses were mostly measured by the severity of alopecia tool (SALT) with a score < 10 defined as complete response ( Table 4 ) [ 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 ]. Noticeably, 13 pediatric patients were treated effectively with dupilumab [ 172 , 173 , 174 , 175 , 176 , 177 ].…”
Section: Resultsmentioning
confidence: 99%
“…45 Remission of alopecia universalis was also reported during dupilumab treatment in some AD patients, indicated the potential relations between Th2 immunity suppression and hair regrowth. [46][47][48][49] By contrast with the hair regrowth after receiving dupilumab, AA was described asa side effect during the dupilumab prescription in AD patients. [50][51][52] The immune pattern and exact efficacy of dupilumab in AA need to be confirmed in larger scales of cases.…”
Section: Dupilumab In Alopecia Areata Treatmentmentioning
confidence: 99%
“…Another study summarized six children with AA and AD received dupilumab treatment for 12.3 months in average, only one patient did not have any improvement at endpoint 45 . Remission of alopecia universalis was also reported during dupilumab treatment in some AD patients, indicated the potential relations between Th2 immunity suppression and hair regrowth 46–49 . By contrast with the hair regrowth after receiving dupilumab, AA was described asa side effect during the dupilumab prescription in AD patients 50–52 .…”
Section: Introductionmentioning
confidence: 99%